Utilization of Continuous Anaerobic Digesters for Processing Cattle Dung and Cabbage (Brassica oleracea) Waste - Tjokorda Sari Nindhia; I Gusti Nyoman Gde Bidura; I Putu Sampurna; Tjokorda Gde Tirta Nindhia (Fermentation, 2025)
The purpose of this work is to explore the addition of cabbage (Brassica oleracea) waste interspersed with cattle dung into a continuous anaerobic digester that normally uses cattle dung as a substrate. In this work, a 200-L continuous anaerobic digester was operated to conduct the research. The digester was filled fully with a mixture of cattle dung and water (50%:50%). The digester was then operated by continuously adding a 5-L mixture of cattle dung and water (50%:50%) every day for 1 month. Subsequently, the digester was operated for 1 month with an additional 5-L mixture of cabbage waste and water (50%:50%) for odd-numbered days and a mixture of cattle dung and water (50%:50%) for even-numbered days. The methane composition was higher (in the range of 41–78%) with only the cattle dung in the system. With the addition of cabbage waste, the methane composition became lower (in the range of 20–60%).